An assessment of the capacity and responsiveness of a national system to address the threat of invasive species: a systems approach - F. Williams; K. L. Constantine; A. A. Ali; T. W. Karanja; S. Kibet; E. K. Lingeera; G. Muthike; I. Rwomushana; J. Godwin; R. Day (CABI Agriculture and Bioscience)
Abstract Background Invasive species affect the social, economic and health aspects of many farmers and are known to cause major losses with considerable costs spent on management. Several international agreements recognise the threat caused by invasive species which signatories have an obligation to manage. This paper sets out a framework and method for assessing the performance and responsiveness of a country’s invasive species system. The objective is to engage with key actors within an invasive species system using a participatory approach to determine the strengths, weaknesses and functioning of the invasive species system. The aim is to understand the system as it currently stands and to identify opportunities and challenges from various actor’s perspectives. Method The first step was to define an invasive species system and its component parts including the functions, expected outputs and contextual factors. A range of indicators and participatory tools were developed to measure system performance. The process includes a desk review, stakeholder workshop and key informant interviews. The approach was piloted in Kenya. Results Actors who are active in managing invasive species were identified and engaged. The assessment process provided insights into the current functioning of the invasive species system. A number of key challenges were identified, for instance, the lack of finance, governance and leadership, as major barriers to effective system performance, alongside the lack of a central coordinating body to guide invasive species management. Conclusion The systems approach developed helped in facilitating the engagement of key actors within a country’s invasive species system. The actors performed a self-assessment of the current system status and determined what is required to move towards more effective management of invasive species. Participants responded positively to the framework and process developed, which contributed to developing ownership and clear steps forward towards a more pro-active, rather than reactive, approach in the management of invasive species.